Analisis Pengendalian Mutu pada Asam Lemak Bebas Minyak Kelapa Sawit Menggunakan Metode SQC - Rizky Syaputra; Sofiyanurriyanti Sofiyanurriyanti Sofiyanurriyanti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
PT. Socfindo Indonesia Seunagan Plantation is a company that produces palm oil and palm kernel (PKO). This observation aims to determine the parameters of free fatty acids in PT. Socfindo Indonesia Seunagan Plantation. Is it within the quality control limits based on the Xbar and Rbar control charts, as well as investigations into the causes of improving the quality of palm oil with Free Fatty Acid (FFA) parameters. Based on the results of the Crude Palm Oil (CPO) quality control chart, the number of samples for free fatty acid levels, according to the control chart Xbar = 2.1375 and Rbar = 1.2308, there are some data that are out of the control limit UCL = 2.7323, CL = 2.1375 LCL = 1.5427 after modification of Xbar and Rbar control chart. Based on the results of observations, interviews and fieldwork, there are five factors that affect the quality of Crude Palm Oil (CPO). The factors themselves are raw materials, work environment, people, machines and work methods and techniques.This case study was conducted on a company that produces palm oil and palm kernel (PKO). This observation aims to determine the parameters of free fatty acids in this company. Observe whether it is within the quality control limits based on Xbar and Rbar control charts. Then, investigate the cause of the increase in the quality of palm oil with the Free Fatty Acid (FFA) parameter. Based on the results of the Crude Palm Oil (CPO) quality control chart, the number of samples for free fatty acid levels, according to the control chart Xbar = 2.1375 and Rbar = 1.2308, there are some data that are out of the control limit UCL = 2.7323, CL = 2.1375 LCL = 1.5427 after modification of Xbar and Rbar control chart. The results of observations show that in interviews and in the field there are five factors that affect the quality of Crude Palm Oil (CPO). The factors themselves are raw materials, work environment, people, machines and work methods and techniques.